THE EFFECT OF USING SONGS TO INCREASE YOUNG LEARNERS’ VOCABULARY ACHIEVEMENT THROUGH WHATSAPP - Hanita Oktaviani (STBA Pontianak, 2021)
Teaching young learners can be a challenge due to their cognitive development. Thus, teachers need to be creative in using approach and methodology in teaching young learners. Songs are regarded as one of effective medias to teach young learners. They offer various advantages in the teaching process especially for children. One of the advantages of using songs is that it can increase the students’ interest; hence, stimulate their motivation to learn. This study aims to verify these claims and confirm the effectiveness of using songs to increase young learners’ vocabulary achievement. In order to achieve this goal, quantitative with quasi experimental is used as the design for the research. This design includes pre-test, treatment and post-test. The participant of this research is forty students from Madrasah Ibtidaiyah Swasta (MIS) Litahfidzhil Qur’an Darussalam which divided into two classes. One class is the experimental class, the other is the control class. The data were analyzed using a t-test. The findings indicate that songs offer positive effect on young learners’ vocabulary achievement. Therefore, based on the finding of this study, it is suggested for teachers who teach young learners to occasionally use songs to teach English due to its effectiveness in increasing learners’ vocabulary achievement.